PENGARUH MEDIA PEMBELAJARAN FLASH CARD TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SDN PONDOK BAHAR 3 - Aida Nabila; Dilla Fadhillah; Boy Dorahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Discussing facts and opinions in Indonesian language lessons often makes the classroom atmosphere feel rigid. To break this pattern, Flash Cards come as a simple yet powerful medium that sparks learning interactions. With their colors, images, and easy-to-remember format, Flash Cards are expected to boost motivation and help students clearly distinguish between facts and opinions. A quasi-experimental design with a Nonequivalent Control Group Design was applied in this study, involving 66 fifth-grade students of SDN Pondok Bahar 3 in the 2024/2025 academic year. Class VA served as the experimental group using Flash Cards, while Class VB acted as the control group. The research instrument consisted of 25 multiple-choice questions that had been validated to measure learning outcomes. Data analysis using a t test revealed that the pretest results showed no significant differences, while the posttest indicated a meaningful gap with a t value of 2.977 higher than the t table of 1.997. These findings confirm that Flash Cards are not merely colorful pieces of paper, but a creative strategy that strengthens comprehension and enhances student achievement in learning facts and opinions.